Modulation of cytomegalovirus immune evasion identifies direct antigen presentation as the predominant mode of CD8 T-cell priming during immune reconstitution after hematopoietic cell transplantation - Holtappels, Rafaela; Büttner, Julia K.; Freitag, Kirsten; Reddehase, Matthias J.; Lemmermann, Niels A. (Frontiers in Immunology, 2024)
Cytomegalovirus (CMV) infection is the most critical infectious complication in recipients of hematopoietic cell transplantation (HCT) in the period between a therapeutic hematoablative treatment and the hematopoietic reconstitution of the immune system. Clinical investigation as well as the mouse model of experimental HCT have consistently shown that timely reconstitution of antiviral CD8 T cells is critical for preventing CMV disease in HCT recipients. Reconstitution of cells of the T-cell lineage generates naïve CD8 T cells with random specificities among which CMV-specific cells need to be primed by presentation of viral antigen for antigen-specific clonal expansion and generation of protective antiviral effector CD8 T cells. For CD8 T-cell priming two pathways are discussed: "direct antigen presentation" by infected professional antigen-presenting cells (pAPCs) and "antigen cross-presentation" by uninfected pAPCs that take up antigenic material derived from infected tissue cells. Current view in CMV immunology favors the cross-priming hypothesis with the argument that viral immune evasion proteins, known to interfere with the MHC class-I pathway of direct antigen presentation by infected cells, would inhibit the CD8 T-cell response. While the mode of antigen presentation in the mouse model of CMV infection has been studied in the immunocompetent host under genetic or experimental conditions excluding either pathway of antigen presentation, we are not aware of any study addressing the medically relevant question of how newly generated naïve CD8 T cells become primed in the phase of lympho-hematopoietic reconstitution after HCT. Here we used the well-established mouse model of experimental HCT and infection with murine CMV (mCMV) and pursued the recently described approach of up- or down-modulating direct antigen presentation by using recombinant viruses lacking or overexpressing the central immune evasion protein m152 of mCMV, respectively. Our data reveal that the magnitude of the CD8 T-cell response directly reflects the level of direct antigen presentation.